Shaping Global Perceptions: A Sentiment Analysis of Indonesian Made Boots - Indrajit (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to explore customers’ perception toward an Indonesian handmade shoes and brand image created after seeing the review made by a foreign customer who happens to be a Youtuber. This study is Adopting a qualitative sentiment analysis method by analyzing comments from YouTube reviews that have been cleaned up using Atlas.ti. The study interprets user-generated comments to understand consumer perception and brand image after categorizing sentiments into positive, negative, neutral and supplements them with descriptive coding for deeper insights. Findings show that consumers predominantly express positive sentiments, highlighting craftsmanship and brand uniqueness, while negative comments focus on limited size availability, long waiting time and ordering difficulty. This study provides insights into how other local brands can enhance their market presence through effective storytelling, leveraging cultural identity, and partnering with influencers particularly within the context of local products entering global markets. It highlights the importance of brand awareness, emphasizing the role of review credibility and the differential impact of positive vs. negative feedback that may influence purchase intentions.